129 Challenges of monitoring drug use trends and communicating results: Solutions from the National Drug Early Warning System (NDEWS) - Tamara Millay; Linda B. Cottler (Journal of Clinical and Translational Science)
Objectives/Goals: To discuss the challenges faced by National Drug Early Warning System (NDEWS; PI Cottler) in monitoring emerging drug trends and disseminating data to maximize public health impact. Drug trends are constantly in flux, with various communities facing different harms. To provide salient information, NDEWS must triangulate data from multiple sources. Methods/Study Population: In 2020, NDEWS was funded at University of Florida through a cooperative agreement with NIDA. A Scientific Advisory Group meets regularly for overall guidance, and 17 Sentinel Sites provide local perspectives. Now in its fifth year, NDEWS has utilized traditional data such as death reporting and drug seizures and has launched several novel surveillance components. Rapid Street Reporting conducts anonymous surveys of drug use in a Sentinel Site or hotspot each month. Machine learning methods applied to Reddit reveal new trends and novel substances. County-level alerts are generated by analysis of 911-dispatch data accessed through biospatial.io. Wastewater-based epidemiology provides city-level data. Findings are disseminated primarily through email weekly briefings and by peer-reviewed articles. Results/Anticipated Results: In its first iteration, NDEWS has expanded available data sources and worked to integrate data to reveal trends that impact communities across the USA. These patterns vary substantially over time and by region and population, complicating analysis, but inclusion of multiple data sources is imperative for a full understanding of the landscape. NDEWS continues to explore novel routes of disseminating information to those who need it, including contacting local health departments with high overdose rates. Establishing networks for bidirectional communication with stakeholder groups such as toxicologists and educational affiliates is underway. NDEWS seeks to deepen ties with survivors unions (those with lived experience) and harm reduction organizations, which can be difficult due to mistrust of research. Discussion/Significance of Impact: Monitoring the rapidly changing drug landscape in the USA is challenging, and its importance has only grown in recent years as new substances arise and adulterated drug supply has become the norm, promulgating the rise of dangerous substances such as fentanyl and xylazine. Ensuring that information filters out to those who use substances is critical.